2014
DOI: 10.1055/s-0034-1368350
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of the Effect of Puerarin on Hepatic Cytochrome P450-Mediated Drug Metabolism

Abstract: Puerarin (8-β-D-glucopyranosyl-7-hydroxy-3-(4-hydroxyphenyl)-4H-1-benzopyran-4-one) is a major pharmacological component of Puerariae Radix, the root of Pueraria lobata. We investigated the effect of puerarin on hepatic cytochrome P450-mediated drug metabolism in rats and humans. The in vitro cytochrome P450 inhibitory effect of puerarin in human and rat liver microsomes was evaluated using the following model cytochrome P450 substrates: phenacetin for CYP1A, diclofenac for CYP2C, dextromethorphan for CYP2D, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Kim et al . () carried out an in vitro investigation to determine the CYP inhibitory potential of puerarin on variety of substrates using human and rat liver microsomes. The probe substrates consisted of diclofenac, dextromethorphan, testosterone and phenacetin for CYP2C, CYP2D, CYP3A and CYP1A, respectively.…”
Section: Individual Case Studies Of Flavonoidsmentioning
confidence: 97%
See 1 more Smart Citation
“…Kim et al . () carried out an in vitro investigation to determine the CYP inhibitory potential of puerarin on variety of substrates using human and rat liver microsomes. The probe substrates consisted of diclofenac, dextromethorphan, testosterone and phenacetin for CYP2C, CYP2D, CYP3A and CYP1A, respectively.…”
Section: Individual Case Studies Of Flavonoidsmentioning
confidence: 97%
“…Regardless of buspirone dosing route, puerarin caused an inhibition of buspirone metabolism resulting in a higher oral bioavailability. Hence, the CYP3A related inhibitory potential of puerarin was unequivocally demonstrated after a mere single intravenous dose administration (Kim et al ., ).…”
Section: Individual Case Studies Of Flavonoidsmentioning
confidence: 99%
“…The femoral artery and vein of the rats were cannulated with a polyethylene tube (Becton Dickinson Diagnostics, Sparks, MD, U.S.A.) under anesthesia with Zoletil (20 mg/kg, intramuscular injection) (Virbac, Carros, France). 15) Rats were given a single intravenous dose (via the femoral vein; 5 mg/ kg) or an oral dose (using a feeding tube; 20 mg/kg) of buspirone (dissolved in normal saline). An approximately 250 µL aliquot of blood samples was collected via the femoral artery at predetermined time points (0, 1, 5, 15, 30, 45, 60, 90, 120, 180 min for the intravenous study; 0, 2, 5, 10, 15, 20, 30, 45, 60, 90, 120 min for the oral study).…”
Section: Methodsmentioning
confidence: 99%
“…12,15) However, in these previous studies, full bioanalytical method validation data were not provided, and chromatographic conditions and sample preparation procedures were randomly selected without optimization. Moreover, the sensitivity of our previous methods (LOQ=100 ng/ mL) was not sufficient for lower-dose preclinical study, which needed further improvement.…”
Section: Representative Chromatograms Of Buspirone and Is In Rat Plmentioning
confidence: 99%
“…22) Control or 1,25(OH) 2 D 3 -treated rats (n=4 in each group) were given a single intravenous dose (15 µmol/kg as adefovir) of [ In Situ Closed Loop Study in Rats In situ closed loop study was conducted as previously reported. [23][24][25] Briefly, after a minimal abdominal incision was made under light ether anesthetization and the contents within the gastrointestinal (GI) tract were sufficiently washed, a 5-cm long duodenum, jejunum or ileum loop was closed by ligation approximately 2 cm distal to both ends of each intestinal section.…”
Section: Methodsmentioning
confidence: 99%